2023
DOI: 10.3390/antiox12101841
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum horneri Extract Attenuates Depressive-like Behaviors in Mice Treated with Stress Hormone

Inhye Park,
Jiwoo Kim,
Minji Kim
et al.

Abstract: Sargassum horneri, a brown seaweed, is known for its various health benefits; however, there are no reports on its effects on depression. This study aimed to investigate the antidepressant effects of S. horneri ethanol extract (SHE) in mice injected with corticosterone (CORT) and to elucidate the underlying molecular mechanisms. Behavioral tests were conducted, and corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and CORT levels were measured. A fluorometric monoamine oxidase (MAO) en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The Caryophyllus aromaticus extract with a total flavonoid content of 9381.70 mg QE-Eq/g provides antidepressant effects in albino rats [52]. Sargassum horneri and Zataria multiflora extracts have also been shown to reduce depressive-like behaviors in animal models of stress [53,54]. Lychee peel extract with 90.05 ± 0.26 mg QE-Eq/g total flavonoid content reduces depressive-like behavior in chronic restraint stress-subjected rats [48].…”
Section: Discussionmentioning
confidence: 99%
“…The Caryophyllus aromaticus extract with a total flavonoid content of 9381.70 mg QE-Eq/g provides antidepressant effects in albino rats [52]. Sargassum horneri and Zataria multiflora extracts have also been shown to reduce depressive-like behaviors in animal models of stress [53,54]. Lychee peel extract with 90.05 ± 0.26 mg QE-Eq/g total flavonoid content reduces depressive-like behavior in chronic restraint stress-subjected rats [48].…”
Section: Discussionmentioning
confidence: 99%
“…(94) In animal models, treatment with extract from the brown seaweed Sargassum horneri (500 mg/kg) for 3 weeks prevented the loss of neurotransmitters such as serotonin, dopamine, and norepinephrine in the mouse brain, as well as improvements in depressive-live behaviours caused by an intraperitoneal injection of corticosterone. (95) The authors performed a quantitative analysis and verified the presence of fucoxanthin in the extract. That study further revealed that the underlying mechanism involved the activation of the ERK-CREB-BDNF pathways by the brown seaweed extract.…”
Section: Depression and Anxietymentioning
confidence: 99%